Computional modeling of University budget and finance - Ivanauskas, Feliksas; Pikturna, Aleksas; Valiulis, Karolis (Lietuvos matematikos rinkinys, 2013)
The discrete time mathematical model describing fundamental processes of the university, i.e. interdynamics among students, lectures and finances is presented. The model consists of three differential equations.